Pelaksanaan Program Pemerintah Bantuan Operasional Sekolah (BOS) di SMP Negeri 1 Desa Jejawi Kabupaten Ogan Komering Ilir - Ahmad Yani Kosali (LPPM STIE PERTIBA Pangkalpinang, 2019)
One of the goals of the establishment of the Indonesian state. In order to increase the dignity and status of the Indonesian people, unceasingly strives for the entire population to receive an education. The efforts made by the government are issuing programs in education. The government issued a program that is expected to improve education, namely the school grants program (BOS). BOS management is the responsibility of every school managed by the School Principal, School Treasurer, and School Committee. This research is descriptive qualitative research, aimed to find out the implementation of the BOS program in SMP Negeri 1 Jejawi Village, Ogan Komering Ilir Regency and the factors that hinder the implementation of the program. Data collection techniques used: observation, interviews, and study documents or libraries. Based on the results of the study, it is known that the implementation of the BOS program in SMP Negeri 1 Jejawi Village, Ogan Komering Ilir Regency has been carried out in accordance with government regulations. Starting from the preparation of the BOS management team, preparing RKAS, to making accountability reports that are in accordance with existing regulations. Its activity programs do not deviate from existing rules. There were no obstacles felt by SMP Negeri 1 Jejawi Village, Ogan Komering Ilir Regency in the implementation of the BOS program, even if there could still be overcome so that the implementation of the BOS program could run well.